1986
DOI: 10.1128/jcm.24.5.856-858.1986
|View full text |Cite
|
Sign up to set email alerts
|

Biotype and serogroup distribution of Campylobacter isolates from children in Nigeria

Abstract: A total of 101 Campylobacter isolates from Nigerian children with or without gastroenteritis were biotyped and serogrouped by using the Lior typing schemes (H.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The serogroups found in sheep in this study were similar to those reported in domestic animals previously in Nigeria (Adegbola et al, 1990(Adegbola et al, , 1991 and in humans (Alabi et al, 1986;Coker and Adefoso, 1994).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The serogroups found in sheep in this study were similar to those reported in domestic animals previously in Nigeria (Adegbola et al, 1990(Adegbola et al, , 1991 and in humans (Alabi et al, 1986;Coker and Adefoso, 1994).…”
Section: Discussionsupporting
confidence: 90%
“…Several epidemiological studies in developed countries have identi®ed sources of Campylobacter enteritis in man to include animals, food, water, and milk products (Khan, 1982;Skirrow, 1982). Although there are sporadic reports of Campylobacter enteritis in developing countries particularly Nigeria (Olusanyo et al, 1983;Alabi et al, 1986;Ani et al, 1988), very little is known concerning its mode of spread.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C'ampylobacter jejuni is an important case of acute diarrhoeal disease occurring in both sporadic and epidemic form (Blaser et al 1983;Svedhem & Kaijser, 1980;Skirrow, 1987;. Repeated enteric infection with this organism is particularly prevalent in children in developing countries where most of the cases occurring in children over 2 years old are asymptomatic (Glass et al 1983;Calva et al 1988;Mathan et al 1984; Georges-Courbot et Alabi et al 1986). It has been claimed that different strains appear in the repeated infections, but that a limited number of serotypes dominate (Blaser et al 1986;Karmali et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…In Canada, also, three of our leading serovars from patients were found among the top five (7, 4, 1, 36, 2) (Lior 1984a). Serovars 36 and 4 were by far the most predominant types found in cases of enteritis in hospitalized children in Nigeria (Alabi et al 1986), and serogroups 4 and 9 have been reported as the aetiological agents of an outbreak in the USA (Blaser & Patton 1985).…”
Section: Discussionmentioning
confidence: 97%